Comparison Of Islamic Inheritance Law System And Civil Inheritance Law In Realizing Justice And Legal Certainty In Indonesia - Amrullah; Subianta Mandala (Yayasan Cendekia Gagayunan Indonesia, 2025)
A crucial component of the legal system that governs how the testator's posthumous assets are divided among his heirs is inheritance law. Indonesia now has two different systems of inheritance law in place: civil inheritance law and Islamic inheritance law. Islamic inheritance law is based on the Qur'an, Hadith, and the Compilation of Islamic Law (KHI), whereas civil inheritance law is regulated by the Civil Code (KUHPer). These two systems have differences principles, distribution mechanisms, and dispute resolution. These differences are often a source of problems in practice, especially for people between the two legal systems. Therefore, the purpose of this study is to compare Indonesian civil and Islamic inheritance laws in order to give a more thorough understanding of their traits, parallels, and divergences. The study employs a comparative legal perspective and a normative legal research methodology. The legal provisions found in both Islamic and civil law's inheritance-related laws and regulations are examined using the normative legal approach. To find the distinctions and parallels between the two legal systems, a comparative legal technique is also employed. This study's data sources include secondary legal documents like books and pertinent periodicals, as well as main legal materials like the Indonesian Compilation of Laws, the Civil Code, and other laws. It is anticipated that this study will aid in the development of Indonesian inheritance law, particularly by offering suggestions for initiatives to unify civil and Islamic inheritance laws in order to establish legal clarity and fairness in the distribution of inheritance in society